Soluble amyloid beta-containing aggregates are present throughout the brain at early stages of Alzheimer's disease. Issue 3 (2nd July 2021) - Sideris, Dimitrios I; Danial, John S H; Emin, Derya; Ruggeri, Francesco S; Xia, Zengjie; Zhang, Yu P; Lobanova, Evgeniia; Dakin, Helen; De, Suman; Miller, Alyssa; Sang, Jason C; Knowles, Tuomas P J; et al.
Abstract: Protein aggregation likely plays a key role in the initiation and spreading of Alzheimer's disease pathology through the brain. Soluble aggregates of amyloid beta are believed to play a key role in this process. However, the aggregates present in humans are still poorly characterized due to a lack of suitable methods required for characterizing the low concentration of heterogeneous aggregates present. We have used a variety of biophysical methods to characterize the aggregates present in human Alzheimer's disease brains at Braak stage III. We find soluble amyloid beta-containing aggregates in all regions of the brain up to 200 nm in length, capable of causing an inflammatory response. Rather than aggregates spreading through the brain as disease progresses, it appears that aggregation occurs all over the brain and that different brain regions are at earlier or later stages of the same process, with the later stages causing increased inflammation. Abstract : Sideris et al. report that soluble inflammatory amyloid beta-containing aggregates are found in all regions of early Alzheimer's disease brain. Aggregation may therefore be occurring all over the brain simultaneously, with different brain regions being in different stages of the same process, with the later stages causing increased inflammation. Graphical Abstract: